Cyber security management a governance, risk and compliance framework - Trim, Peter R. J.; Lee, Yang-Im (Gower, 2014)
Cyber Security Management places security management in a holistic context and outlines how the strategic marketing approach can be used to underpin cyber security in partnership arrangements.